Tranformation of a health sciences postgraduate population (2008-2017) at a higher education institution in South Africa: Has this occurred? - Meela, M.; Libhaber, E.; Kramer, B. (South African Journal of Higher Education, 2021)
Despite efforts to prioritise transformation of the previously disadvantaged population, inequalities created by the Apartheid system persist in the South African higher education system. This study assessed transformation in relation to population affinity and gender of first-time enrolments of Health Sciences (HS) postgraduate students at the University of the Witwatersrand (Wits), Johannesburg. A retrospective study of the Wits HS postgraduate student database was used for this assessment. The probability of a postgraduate student being Black African increased by 7.5 per cent per year [OR: 1.075, 95% CI (1.052–1.099), p<0.001] over the period 2008–2017 and of being female, increased by 5.6 per cent per year [OR: 1.056, 95% CI (1.033–1.081), p<0.001]. While transformation has occurred, Black African females are still under-represented. The transformation of the postgraduate student body as observed in this study is of importance to other countries struggling with racial and gender equity in the health workforce.